Analisis Model Discovery Learning Pada Pembelajaran Akidah Akhlak Terhadap Peningkatan Pemahaman Dan Karakter Peserta Didik - Munawir; Nafilatus Sa’adah; Reyhanatul Jannah (Fakultas Tarbiyah Institut Agama Islam Hamzanwadi NW Pancor, 2023)
This research aims to apply the Discovery Learning model in learning Aqidah Akhlak and its impact on increasing students' understanding and character. The research method used is descriptive qualitative and literature study. The research sample consisted of students at elementary school level in Surabaya. Based on the literature reviewed from several journals, the research results show that the application of the Discovery Learning model significantly increases students' understanding in learning Aqidah Akhlak. Apart from that, the Discovery Learning model also has a positive impact on the character of students. Students show improvements in character aspects such as curiosity, independence, cooperation, and problem-solving abilities. The findings of this research indicate that the Discovery Learning model is effective in increasing students' understanding and forming positive characters in learning Aqidah Akhlak. Therefore, it is recommended for educators to consider using the Discovery Learning model as an alternative learning approach that can enrich students' learning experiences and improve learning outcomes in the Aqidah Morals subject. Keyword: Discovery Learning; Character; Moral Creed; Effective.